Ethnographic approximation to the construction of the female and male identities in Primary Education - Sanchez Alvarez, Iriana (Revista Complutense de Educación, 2018)
In the primary education stage the children learn to be socially identifiable like girl or boy, beginning to construct its gender identity. From this perspective, the article presents the results of an ethnografhic investigation that was realized in a center of primary education of the the Asturias to know the process of construction of the feminine and masculine identities. In addition participant observation realized along an academic course in 5th and 6th of primary, also groups of discussion were realized with al whole of 28 children and girls. The results have allowed to conclude that the boys and the girls are shaping its genre identity across the partners/experts influences teachers, and different activities, methods and materials used in the school context. Also we have concluded that, in general, some and others make themselves comfortable to the roll of socially established hegemonic genre, hoping to fit between its equal ones and please the adults who surround them. Nevertheless, there are also students that there transgress the genre norms what provoques that they have difficulties un the social interaction processes with its equal ones, especially the boys whose it collaborates to the homosexuakity. Before this reality, we consider the genre work to be necessary in the school, of form holística, from the first ages for to right, the category genre (Connell, 1996, 2000) sice the school centers constitute central spaces for the development of al counterhegemonic speech.